Stink and the Incredible Super-Galactic Jawbreaker [Smraďo anglicky] / Book 2. - McDonald, Megan (Walker Books Ltd, 2020)
Meet Judy Moody's brother! Welcome to Planet Jawbreakersw!When Stink buys a mammoth jawbreaker that doesn't break his jaw, he writes a letter of complaint to the manufacturer and receives a ten-pound box of 21,280 jawbreakers for his trouble! This unexpected benefit of acing the art of letter-writing in school sure gets Stink thinking. Soon Stink is so preoccupied with getting free stuff sent to him that he overlooks a scribbly envelope in the mail pile until his best friend, Webster, starts acting standoffish and looks as mad as a hornet.In this hilarious episode from Megan McDonald and Peter H. Reynolds, Judy Moody's shorter sibling truly comes into his own. As a delightful bonus for both teachers and kids, thirty-six common idioms from "two heads are better than one" to "a leopard can’t change its spots" are sprinkled throughout the story; seven of the idioms are humorously illustrated by Stink, and all are listed at the end to inspire a search for idioms that’s more fun than a barrel of monkeys.